URGENCY OF SHARIA FINANCIAL AUDITORS IN INDONESIA - Abu Bakar (Jurnal Akuntansi Dan Bisnis Indonesia (JABISI), 2023)
This research is descriptive research that aims to discuss and analyze the basic concepts of Islamic economics, whether or not Islamic auditors are needed, how the code of ethics of Islamic auditors works, Islamic financial standardization and the need for Islamic auditor standardization. The results of the study show that Islamic business is very different from conventional business where the main purpose of doing business is in the context of worshiping Allah and not mere consideration of profit, both of which require urgent Sharia auditors because the existing Sharia business entities are not comparable to the number of existing Sharia auditors. The three Sharia auditors require a code of ethics that is different from the conventional audit code of ethics. The Islamic Financial Accounting Standards issued by the Central Executive of the Indonesian Institute of Accountants will continue to develop in line with Sharia business practices in Indonesia. Fifth, there is a need for standardization of Sharia Accountants to maintain professionalism in conducting Sharia audits.